Customer satisfaction with Restaurants Service Quality during COVID-19 outbreak: A two-stage methodology. (August 2022) - Zibarzani, Masoumeh; Abumalloh, Rabab Ali; Nilashi, Mehrbakhsh; Samad, Sarminah; Alghamdi, O.A.; Nayer, Fatima Khan; Ismail, Muhammed Yousoof; Mohd, Saidatulakmal; Mohammed Akib, Noor Adelyna
Abstract: Online reviews have been used effectively to understand customers' satisfaction and preferences. COVID-19 crisis has significantly impacted customers' satisfaction in several sectors such as tourism and hospitality. Although several research studies have been carried out to analyze consumers' satisfaction using survey-based methodologies, consumers' satisfaction has not been well explored in the event of the COVID-19 crisis, especially using available data in social network sites. In this research, we aim to explore consumers' satisfaction and preferences of restaurants' services during the COVID-19 crisis. Furthermore, we investigate the moderating impact of COVID-19 safety precautions on restaurants' quality dimensions and satisfaction. We applied a new approach to achieve the objectives of this research. We first developed a hybrid approach using clustering, supervised learning, and text mining techniques. Learning Vector Quantization (LVQ) was used to cluster customers' preferences. To predict travelers' preferences, decision trees were applied to each segment of LVQ. We used a text mining technique; Latent Dirichlet Allocation (LDA), for textual data analysis to discover the satisfaction criteria from online customers' reviews. After analyzing the data using machine learning techniques, a theoretical model was developed to inspect the relationships between the restaurants' quality factors and customers' satisfaction. In this stage, Partial Least Squares (PLS) technique was employed. We evaluated the proposed approach using a dataset collected from the TripAdvisor platform. The outcomes of the two-stage methodology were discussed and future research directions were suggested according to the limitations of this study. Highlights: Customer Satisfaction and Restaurants Service Quality during COVID-19 Outbreak. The Use of Social Data for Analyzing Customer Satisfaction. Moderation Effect of COVID-19 Safety Precautions on Restaurants' Quality Dimensions and Satisfaction. A New Two-Stage Methodology Using PLS-SEM and Machine Learning.